Per Jacobsson Lecture : Latin America: Outlook and Challenges Ahead - Reinhart, Carmen; Valdes, Rodrigo (Washington, D.C. : International Monetary Fund, 2017)
Latin America: Outlook and Challenges Ahead.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet